Finite Element Analysis of the Deformation Behavior of the Up and Down Roll Differential Diameter Rolling for Medium Plate. (October 2020) - Wang, Weihua; Lu, Shiping
Abstract: In order to realize the rolling technology with different reduction of upper and lower surface in the production of medium and heavy plate, a rolling technology with the same rolling line speed and different diameter of upper and lower rolls was adopted in a factory, and good results were achieved. This technology is different from the previous large roll diameter difference rolling and differential speed rolling. Large roll diameter difference rolling is an asynchronous rolling technology, which uses the difference of upper and lower roll diameter to cause the different linear speed of rolling, so as to achieve the purpose of upper and lower pressure rolling. It is mainly used in the production of section steel, and belongs to the asymmetric rolling condition. Under the condition of asymmetric rolling with unequal roll diameter, a three-dimensional large deformation and asymmetric rolling FEM model is established by using the finite element software. The stress and deformation behavior of the deformation area of the steel plate are analyzed. The fiber length changes along the longitudinal direction at different thickness positions and the shape change of steel plate in the rolling process are obtained. The results show that when the diameter of the upper roll is larger than that of the lower roll, the Mises equivalent stress, equivalent plastic strain and the change of the length of the longitudinal fiber in the deformation area are approximate distributed symmetrically along the center of the two sides, the center value of steel plate is small, and the upper and lower surface values are large; the equivalent stress of the lower surface is larger than the upper surface, and the minimum change of the fiber length appears about 1/3 of the thickness from the lower surface. Under the condition of asymmetric up and down rolling, the head of steel plate tends to down-bending. The maximum distance of the steel plate head buckle ∆y is 0.185 m, the bending radius is 6.519m and the bending curvature is 0.153.